ZCT 542/4 - Solid State Theory II - PPSF, Pusat Pengajian Sains Fizik (Universiti Sains Malaysia, 2001)
UNIVERSITI SAINS MALAYSIA Second Semester Examination 2000/2001 Academic Session February/March 2001 ZCT 542/4 - Solid State Theory II Time : 3jam Please check that the examination paper consists of EIGHT printed pages before you commence this examination. Answer any FOUR questions. Candidates may choose to answer all questions in the Malay Language. If candidates choose to answer in the English Language, it is compulsory to answer at least one question in the Malay Language.